1990
DOI: 10.2118/90-03-04
|View full text |Cite
|
Sign up to set email alerts
|

South Jenner Horizontal Wells A Water Coning Case Study

Abstract: Drilling AND COMPLETIONS South Jenner horizontal wells a water coning case study W. RANDY FREEBORN, BOYD RUSSELL and ALAISTAIR J. MacDONALD AEC Oil and Gas Company ABSTRACT AEC has been a Canadian pioneer in the use of horizontal well technology to combat the adverse affects of water coning A medium radius well of 420 m horizontal displacement was drilled in July 1987 and has been produced at controlled rates since that time. A follow up tong radius well with a horizontal displacement of 1042 m was drilled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Horizontal wells have been used to produce oil from these offshore heavy oil reservoirs, and many field cases have demonstrated the advantages of the horizontal wells compared to the vertical wells [14][15][16][17][18]. However, horizontal wells also face technical, environmental, and economic challenges in oil-water treatment and water disposal caused by water cresting problem [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal wells have been used to produce oil from these offshore heavy oil reservoirs, and many field cases have demonstrated the advantages of the horizontal wells compared to the vertical wells [14][15][16][17][18]. However, horizontal wells also face technical, environmental, and economic challenges in oil-water treatment and water disposal caused by water cresting problem [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Makinde et al, 2011 numerically studied the performance of a horizontal well after breakthrough of water and further performed sensitivity analysis by setting a base case model and varying reservoir parameters (oil production rate, vertical and horizontal permeability, length of perforation, height above perforation, area extent of reservoir and the porosity of the formation) and production rate independently. Freeborn et al, 1990, undertook a case study of water cresting in South Jenner pool, a thin oil rim reservoir with thick bottom water. Medium and long radii wells of 420 m and 1042 m horizontal displacements respectively were drilled to determine their inflow performances compared to a vertical well in the presence of bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the water cut over time for each well was not reported. (Freeborn et al, 1990) numerically investigated different placement of the horizontal well from the top of the reservoir and observed that there was a decline in oil reserves produced when the well is closer to the OWC and water cresting is more likely to occur faster due to the upward water flood provided by the bottom water. A more comprehensive and general review on cresting can be found in (Makinde et al, 2011, Permadi andJayadi, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation